No place for a lady : the life story of archaeologist Marjorie F. Lambert - Tisdale, Shelby J. (University of Arizona Press, 2023)
"Marjorie Lambert's life story is intricately involved in the development of archaeology and institutional building in the American Southwest. She became a professional archaeologist and museum curator and was successful at both when relatively few women were able to enter either of these professions"--